The effect of a booster intervention to promote hearing protection behavior in operating engineers1. Issue 2 (5th July 2012) - Hong, OiSaeng; Chin, Dal Lae; Fiola, Lauren A.; Kazanis, Anamaria S.
Abstract Background Booster interventions may be useful in promoting workers' hearing protection device (HPD) use. Previous research on the effectiveness and the optimal timeframe for boosters is limited and inconsistent. Methods In this randomized controlled trial, 403 workers were assigned to receive an individually tailored booster, a control booster, or no booster. The booster intervention groups were further divided by timeframe. Frequency of HPD use was measured 12 months post‐intervention. Results The booster intervention groups significantly accounted for the variance in HPD use in Year 2. Workers in middle‐term booster (67–94 days) group reported a significantly greater increase in HPD use in Year 2 than those in other timeframes, when potential covariates were controlled for. Conclusions Booster intervention letters mailed between 67 and 94 days post‐initial intervention may promote HPD use among participants. Future research should explore additional factors associated with optimal booster design, including more innovative mobile and internet‐based approaches. Am. J. Ind. Med. 56:258–266, 2013. © 2011 Wiley Periodicals, Inc.